Fabrication of biomimetic polysiloxane-bioactive glass–chitosan hybrid monoliths with high apatite-forming bioactivity. (July 2015) - Chen, Jing; Que, Wenxiu; Xing, Yonglei; Lei, Bo
Abstract: The development of biomimetic hybrid implants with high bioactivity is very important for successful bone tissue regeneration. This paper presents a simple strategy for fabricating polydimethylsiloxane–bioactive glass–chitosan hybrid monoliths by a facile sol–gel process. Here, chitosan, which is a critical component in human body, is a natural biocompatible polymer and glycosaminoglycans. Our results indicate that the as-fabricated hybrid monoliths have a porous structure and crack-free morphology, and the in vitro bioactivity test demonstrates that the novel hybrid monoliths have a high apatite-forming ability in simulated body fluid. The facile synthesis, biomimetic structure and composition, as well as high bioactivity of the as-fabricated hybrid monoliths make them promising materials for applications in bone tissue regeneration.